MeetAlive: Room-Scale Omni-Directional Display System for Multi-User Content and Control Sharing - Fender, Andreas Rene; Benko, Hrvoje; Wilson, Andy (Proceedings of the 2017 ACM International Conference on Interactive Surfaces and Spaces, 2017)
MeetAlive combines multiple depth cameras and projectors to create a room-scale omni-directional display surface designed to support collaborative face-to-face group meetings. With MeetAlive, all participants may simultaneously display and share content from their personal laptop wirelessly anywhere in the room. MeetAlive gives each participant complete control over displayed content in the room. This is achieved by a perspective corrected mouse cursor that transcends the boundary of the laptop screen to position, resize, and edit their own and others' shared content. MeetAlive includes features to replicate content views to ensure that all participants may see the actions of other participants even as they are seated around a conference table. We report on observing six groups of three participants who worked on a collaborative task with minimal assistance. Participants' feedback highlighted the value of MeetAlive features for multi-user engagement in meetings involving brainstorming and content creation.